IMAGING OF DEEP VENOUS THROMBOSIS - Abdullah, BJJ (The ASEAN Journal of Radiology, 2023)
We will review the importance early diagnosis of deep venous thrombosis (DVT), the various imaging modalities used and the current imaging protocol used in the diagnosis of DVT in the different groups of patients. Approximately 80% lower extremity DVT is confined to the calf veins and either lyse spontaneously or organise focally with no further sequelae.’ However the remaining 20% accounts for 90% of pulmonary emboli. Optimal treatment would require prevention and early diagnosis of DVT since a mortality of 30% has been reported if pulmonary embolism is untreated compared to 8% if properly diagnosed and treated. There have been numerous different imaging methods used in the diagnosis of deep vein thrombosis (DVT). These include: -